1984
DOI: 10.1104/pp.76.3.658
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Metabolism of the Marine Microalga Chlorella autotrophica

Abstract: The levels of glutamine synthetase (GS) and glutamate dehydrogenase (GDH) in Chlorella autotrophica (clone 580) are strongly regulated by the nitrogen source and salt concentration of the medium. GS is present at high levels in NOj--grown cells, and at maximum levels in nitrogenstarved cells. However, the levels of GS in these cells are somewhat decreased by increasing salinity. Cells growing on NH4W have high NADPH-GDH activity, the levels of which increase with increasing NH4' supply, while GS decreases to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
(35 reference statements)
2
29
1
Order By: Relevance
“…One of the major objections to the proposal that NADPH-GDH plays a significant role in nitrogen assimilation in algae is its high apparent K^^ for ammonium (Mifiin & Lea, 1976;Stewart et al 1980). The apparent K^ for ammonium of NADPH-GDH isolated from Chlorella autotrophica was found to be very high (20 mM; Ahmad & Hellebust, 1984). However, Everest & Syrett (1983) recently reported that NADPH-GDH from Stichococcus bacillaris Naeg.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the major objections to the proposal that NADPH-GDH plays a significant role in nitrogen assimilation in algae is its high apparent K^^ for ammonium (Mifiin & Lea, 1976;Stewart et al 1980). The apparent K^ for ammonium of NADPH-GDH isolated from Chlorella autotrophica was found to be very high (20 mM; Ahmad & Hellebust, 1984). However, Everest & Syrett (1983) recently reported that NADPH-GDH from Stichococcus bacillaris Naeg.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetase activity of GS was determined by the procedure described previously (Ahmad & Hellebust, 1984, 1985. The activities of NADPH-and NADH-GDH were determined at pH 7 5 and 8-1, respectively, by the spectrophotometric method described previously (Ahmad & Hellebust, 1984, 1985.…”
Section: Enzyme Assaysmentioning
confidence: 99%
See 3 more Smart Citations